Squamous cell carcinoma in rare case of Huriez Syndrome: The role of distant flaps - A. Patrignani; D. Ribuffo; A Greco; F. Lo Torto; A. Pagnotta (JPRAS Open)
Context: Huriez syndrome is a rare de rmatological condition characterized by severe sclerotic and atrophic changes in the extremities (hands and feet) and an increased tendency to develop squamous cell carcinomas, with no established gold standard for the surgical treatment of these patients, who are difficult to manage due to the inability to perform reconstructions using local flaps. Clinical Case: We report the case of a patient with severe Huriez syndrome who had developed SCC in both the hands and foot over time. After multiple surgeries at other centers, all resulting in recurrences, we planned wide excisions followed by reconstruction using distant flaps. The postoperative course for both reconstructive procedures was complication-free. Follow-up revealed not only an excellent reconstructive outcome but also highlighted the untapped potential of the flap in managing this condition: thanks to its independent vascularization, the flap remained unaffected by the surrounding diseased skin and significantly improved the scaly, atrophic appearance of the affected areas. Discussion: Huriez syndrome is a dermatological condition characterized by a predisposition to developing squamous cell carcinomas. In these patients, it is essential to plan wide excisions that ensure oncological radicality. The reconstruction must be carefully planned, and microvascular flaps can be prioritized. Conclusion: The radial forearm flap has proven effective for reconstruction in individuals with SCC associated with Huriez syndrome. The skin of the flap not only remained unaffected by the surrounding pathology but also induced a previously undescribed benefit on the diseased skin. This oncological-reconstructive approach could become the gold standard in treating these patients.